Effectiveness of Adlerian Group Guidance Self- Enhancement Module on emotional intelligence of students - Hussein, Abdul Rawuf (2019)
The purpose of this study is to assess the validity and reliability of group guidance module termed Adlerian Group Guidance Self-Enhancement Module (AGG-SE) developed by the researcher based on Sidek Module Development Model (SMDM), and to determine its effect on undergraduate students’ emotional intelligence. The module was examined base on the feedback requested by the researcher from five experts in module development, emotional intelligence, and Adlerian theory, followed by a pilot study conducted to assess the reliability of the module. This study further employed experimental design with randomized pre-test post-test control group design to examine the effectiveness of AGG-SE on students’ ability to perceive, understand, facilitate, and manage emotions in self and others. Respondents were 68 undergraduate male students, who were beneficiaries of Asian Competencies Scholarship Programme (ACSP), targeting the following Southeast Asian countries: Malaysia, Singapore, Indonesia, Philippines, Laos, and Cambodia. The participants age was 18-21 (n: 32), 22-25 (n: 27) and 22-25 (n: 9), all of them were fulltime students at International Islamic University Malaysia (IIUM) and International Islamic College (IIC). Randomized pre-test-post-test experimental design was used, thus, respondents were randomly assigned to experiment [n: 34] and control [n: 34] groups, after administering the 33-Item Schutte Self Report Emotional Intelligence Test (SSEIT) in the pre-test and ensuring equality of variance between the groups. Prior to that, results of the pilot study using confirmatory factor analysis (CFA) on SSEIT revealed that Emotional Intelligence latent construct is a four-factor indexed (χ2/df = 2.127, CFI =.962, TLI =.926, NFI =.969 and RMSEA =.080) indicating a good fit to the model. The results of the reliability and validity of the AGG-SE also revealed an overall validity index of.81, and the Cronbach alpha obtained for the reliability was .605 for 43 items. These results indicated the relevance and fitness of AGG-SE module in addressing students’ emotional intelligence base on the four-factor model revealed by the CFA results. A multivariate analysis of variance (MANOVA) was used to analyse the association between the dependent variables EI sub-dimensions (i.e., perceiving emotion, understanding emotion, managing emotion and facilitating emotion), and the independent variables: 1. the study groups and 2. evaluation of pre-test and post-test, whereas t-test was used to test the effect of study groups, on the EI total. The results of an independent samples t-test demonstrate that after participating in the 12 sessions of AGG-SE, respondents from the experiment group exhibited significant improvement in their emotional intelligence (M = 4.86, SD = .12) compare to their counterpart in the control group (M= 3.83, SD = .35), indicating the effectiveness of the intervention programme AGG-SE, t(37.46) = 15.32, ˂.001. Moreover, the effect of AGG-SE on the ability to perceive, understand, facilitate, and manage emotions varies from high to low scores among the respondents, but EI-Total shows a significant improvement between pre-test and post-test. Nonetheless, comparisons within treatment group across the dependant variables showed that, the respondents highest score was in the ability to perceive emotion (PE) dimension of EI [F (1.59) = 203.288, p ˂.05, partial η2 =.775)], followed by the ability to manage emotion (ME) [F (1.59) = 184.940, p ˂.05, partial η2 =.758] and the ability to understand emotion (UE) [F (1.59) = 145.590, p ˂.05, partial η2 =.712] respectively; although a significant improvement was also observed in the ability to facilitate emotion (FE) dimension of EI [F (1.59) = 116.753, p ˂.05, partial η2 =.664], given the fact that the pvalue reported was ˂ 0.05, the respondents score was lower in the FE dimension compare to the other dimensions of EI. This study confirmed that, AGG-SE was effective in guiding the Asian Competencies Scholarship Program students who were enrolled in various undergraduate programmes in IIUM and IIC to improve their emotional intelligence. It is recommended that school counselling services should not only incorporate emotional competencies in the general school and university counselling framework, but endeavour in developing validated modules to aid counsellors in conducting guidance and counselling programs especially on improving students’ emotional intelligence. Similarly, educational policy makers are encouraged to take proactive roles in ensuring that, students acquire the requisite emotional competencies before joining the workplace. And finally, since the current study was conducted in an academic setting, further studies are needed in the organizational setting, targeting staffs and employees, and perhaps an extended module to test the difference between short time and comprehensive long-time intervention modules.